Penerapan Pidana Bersyarat oleh Hakim Terhadap Pelaku Tidak Pidana Penganiayaan di Pengadilan Negeri Ambon - Hanafi, Hanafi; Kabalmay, Anang; Ridwan, M. (Lembaga Intelektual Muda Maluku, 2024)
The judge has the freedom to determine the type of crime, choose the severity of the crime that moves from the minimum to the maximum in the formulation of the crime concerned. This type of research is field research, the type and source of data, namely primary data, namely interview results, secondary data, namely data obtained through literature, books, and documents related to this research, as well as judges' decisions on conditional crimes. The data analysis technique used in this study is qualitative descriptive, using two analysis techniques, namely inductive and deductive. The results of the data analysis showed that the judge's consideration in imposing a conditional sentence on the perpetrator of the crime of persecution was proven in the court hearing to violate article 351 paragraph (1) of the Criminal Code concerning persecution with a threat of punishment of less than one year. Sentences that are less than one year are not always sentenced to conditional punishment by the judge. The judge's consideration in imposing a conditional sentence on the perpetrator of the crime of persecution is by considering that the perpetrator has admitted his actions, the consequences of the defendant's actions do not endanger the victim, the background of the perpetrator committing the crime and the judge also considers that the defendant has never been punished, the defendant frankly admits his actions and feels regret, the defendant has reconciled and the defendant promises not to commit acts that are against the law